Rules of recognition and legitimacy of the judicial decision in Hart - Simioni, Rafael Lazzarotto (2016)
The proposal for this article is to explore the concept of legitimacy, based on the theoretical framework advanced by Herbert Lionel Adolphus Hart. The question of legitimacy is located at the base of the Democratic State and social interactions, being, at the same time, a complex and extremely important question, approached by several hypothesis and theories, but never reaching a definitive answer. At first, it is observed the necessity of a basis of the legitimacy, and its relation with the concept of justice. This article proceeds to analyze Hart’s vision about primary and secondary rules, and the role of the rules of recognition as a legitimation factor of the legal framework. Lastly, it studies the question of the defeasibility of the legal rules, a phenomenon where some rules take away the effectivity of others, as is the case with the self-defense institute. It is concluded that, although it is not possible, at least for the time being, to find a definitive answer to the question of legitimacy, Hart gives us a sophisticated view, based on social facts, without the need of hypothetical constructs, making it possible to identify, through rules of recognition, the legitimacy embedded in the system.